Se debe incorporar en el código penal del Ecuador, normas que sancionen a padres, tutores, encargados de la tenencia de menores, en casos de transacción en delitos de violencia sexual contra niños, niñas y adolescentes - Cucuri Miñarcaja, Ángel Ernesto (2014)
The objective of this study is to examine how the new criminal justice system in regards to the needs and responses given to girls who are victims of sexual offenses, by tutors, forks and parents; for that reason, I allowed myself especially investigate everything related to sex crimes and injuries in the context of domestic violence, as most of the victims of these crimes have been women, most of them girls. Furthermore this research is directly related to procedural aspects, because if it is true that recent years have been carrying out our reforms country in the field of substantive criminal law on sexual offenses is not less that these improvements have relevantly affected in improved treatment and respect for the rights of women victims, nor better and faster answers to these types of crimes because most are found within the family which are limited to denounce and unpunished, as is common knowledge these crimes taking place in the family are known as incest in criminal law not listed as a crime. I must emphasize that the responsibility is all the social structure and especially the state to adopt legal measures and any other measures in order to have a justice system that respects the rights of children and adolescents, the request of the Company as to recognize the discrimination of women at an early age, an issue that is received in various human rights, this should be a commitment of all social conglomerate legal protection of children and adolescents, which is guaranteed by the tribunals and other public institutions, national courts, the effective protection of girls to be raped by those who have authority over them for different reasons, that at the present time is a difficult pronounced theme solve the arrangements to which come to realize among relatives of the aggressor and the attacked. Access to justice to protect girls who are subjected to rape by tutors, forks and / or family caregivers, is very difficult because these cases are not reported, for which the state must establish special, fair and effective procedures for girls who have been victims of violence, including a timely hearing and effective access to procedures including his mother and one to become an accessory and have the same punishment item author. Although it has been recognized the reforms to the criminal justice that have been carried out in the country in recent times has not been followed up about the rape of girls into the penal system, its features and their suitability to the requirements of due process in a democratic state, hence the interest in evaluating these reforms in the light of gender, in order to identify aspects that they can show to overcome areas of violation of rights of girls and adolescents are yet, in the interest of inquiring into all spaces in which action is needed to overcome the problems that remain, or even be generated with a new system that does not allow this type of crime go unpunished, which for the characteristic of incest, it punishable as rape. This study tries in criminal legislation is recognized as a crime of incest and has the characteristic of a criminal offense and is not random as found today; This is because it takes place within the family and to bequeath to facilitate arrangements between relatives have even been cases that take place between student and teacher who also have reached court settlements made, in which the teacher marries affected and thus solves the problem apparently, because after some time or when the affected reaches age or the assailant raped girl divorces being unprotected; for all these cases it is necessary that the current criminal law for this offense is punished with the maximum penalty that the assembly gets to determine this type of crime carried out by incest is reformed.